Concentrated, 'pulsed' axial glacier flow: structural glaciological evidence from Kvíárjökull in SE Iceland. Issue 13 (4th May 2017) - Phillips, Emrys; Everest, Jez; Evans, David J.A.; Finlayson, Andrew; Ewertowski, Marek; Guild, Ailsa; Jones, Lee
Abstract: A detailed structural glaciological study carried out on Kvíárjökull in SE Iceland reveals that recent flow within this maritime glacier is concentrated within a narrow corridor located along its central axis. This active corridor is responsible for feeding ice from the accumulation zone on the south‐eastern side of Öræfajökull to the lower reaches of the glacier and resulted in a c . 200 m advance during the winter of 2013–2014 and the formation of a push‐moraine. The corridor comprises a series of lobes linked by a laterally continuous zone of highly fractured ice characterised by prominent flow‐parallel crevasses, separated by shear zones. The lobes form highly crevassed topographic highs on the glacier surface and occur immediately down‐ice of marked constrictions caused by prominent bedrock outcrops located on the northern side of the glacier. Close to the frontal margin of Kvíárjökull, the southern side of the glacier is relatively smooth and pock‐marked by a number of large moulins. The boundary between this slow moving ice and the active corridor is marked by a number of ice flow‐parallel strike‐slip faults and a prominent dextral shear zone which resulted in the clockwise rotation and dissection of an ice‐cored esker exposed on the glacier surface. It is suggested that this concentrated style of glacier flow identified within Kvíárjökull has affinities with the individual flow units which operate within pulsing or surging glaciers. © 2017 The Authors Earth Surface Processes and Landforms © 2017 John Wiley & Sons, Ltd.